2020
DOI: 10.1002/adfm.202002230
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Crystallization of Mixed‐Cation Tin Halides for Highly Efficient and Stable Lead‐Free Perovskite Solar Cells

Abstract: As the most promising lead‐free branch, tin halide perovskites suffer from the severe oxidation from Sn2+ to Sn4+, which results in the unsatisfactory conversion efficiency far from what they deserve. In this work, by facile incorporation of methylammonium bromide in composition engineering, formamidinium and methylammonium mixed cations tin halide perovskite films with ultrahighly oriented crystallization are synthesized with the preferential facet of (001), and that oxidation is suppressed with obviously dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 55 publications
(83 reference statements)
2
72
1
Order By: Relevance
“…have further promoted the PCE to 9.31% using FA 0.75 MA 0.25 SnI 3 by introducing Br to inhibit oxidation and passivate defects. [ 41 ] Nakamura et al. have added a dihydropyrazine derivative reacted with SnF 2 additive to boost the PCE up to 11.5%.…”
Section: Introductionmentioning
confidence: 99%
“…have further promoted the PCE to 9.31% using FA 0.75 MA 0.25 SnI 3 by introducing Br to inhibit oxidation and passivate defects. [ 41 ] Nakamura et al. have added a dihydropyrazine derivative reacted with SnF 2 additive to boost the PCE up to 11.5%.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the reduction of Sn vacancies from Sn 4+ to Sn 2+ via a comproportionation reaction by metallic tin [30,31]. Long-chain ammonium cations such as phenylethylammonium, butylammonium, and ethylammonium have also been used to form two-and three-dimensional hierarchy structures that protect tin perovskites from oxidation and passivate the trap states [32][33][34][35][36][37][38][39][40][41]. It has also been reported that the addition of some small organic molecules or polymers, such as trimethylamine [42], CH 3 NH 3 I•3CH 3 NH 2 amine complex [43], the potassium salt of hydroquinone sulfonic acid [44], 8-hydroxyquinoline [45], liquid formic acid [46], pentafluorophenoxyethylammonium iodide [47], or poly(vinyl alcohol) [48] can improve the crystallinity and reduce the defects caused by oxidation, thereby enhancing the stability of the resulting tin perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the corresponding device based on FA 0.75 MA 0.25 SnI 2.75 Br 0.25 shows the PCE of 9.31% compared to 5.02% of the FASnI 3 based control device. [ 194 ] Compared with MASnI 3 and FASnI 3 , FA 0.75 MA 0.25 SnI 3 shows outstanding charge injection property at the perovskite/TiO 2 interface and effectively interfacial charge separation to free carriers, confirmed by high PL quenching efficiency and short PL lifetimes originating from the largest ΔΦ found at FA 0.75 MA 0.25 SnI 3 /TiO 2 interface (Figure 20). [ 190 ] In the view of electronic potential, as more photogenerated electrons are extracted by the ETL under illumination, the surface potential is lifted by excess holes in FA 0.75 MA 0.25 SnI 3 perovskite layer.…”
Section: Band Alignment Protocolsmentioning
confidence: 99%
“…[ 38 ] (MASnBr 3−3 x Cl 3 x ), Ref. [ 194 ] (MA 0.25 FA 0.75 SnI 2.75 Br 0.25 ), Ref. [ 68 ] (FASnI 0.75 Br 0.25 ) and Ref.…”
Section: Band Alignment Protocolsmentioning
confidence: 99%